Principles of Occupational Hygiene : An Introduction - Reed, Susan (Occupational hygienist) (CRC Press, 2025)
"Now in its fourth edition, Principles of Occupational Health and Hygiene:An Introduction allows for early career occupational hygienists and occupational health and safety professionals or students to develop their basic skills and knowledge to anticipate, recognize, evaluate, and control workplace hazards that can result in injury, illness or affect the well-being of workers and the community. It offers a comprehensive overview of occupational health risks and hazardous environments encountered in varying industries. This book is an essential reference for students, early career Occupational Hygienists professionals and anyone in an Occupational Health and Safety role"--